Simulation of the sedative effect of high doses of detomidine in equines - Ferrante, Marcos; Valerias Gaddini, Lucas; Onghero Taffarel, Marilda; Ferrante , Marcos (Pubvet, 2018)
The objective of the study was to simulate the sedative effect of the administration of detomidine in doses of 80 ug/kg by intravenous and intramuscular route in equines. A pharmacokinetic/pharmacodynamic (PK/PD) model was performed with the sigmoid curve of plasma concentration, obtained by Mama and collaborators, depending on the effect on the head position by means of Hill equation. A sedative effect simulation of 80 ug/kg intravenous (IV) and intramuscular (IM) doses by Hill's equation was then performed. Higher and prolonged plasmatic concentrations were obtained after administrations of 80 ug/kg, when compared to administrations of 30 ug/kg resulting in higher and longer effect. The simulation of the effect of detomidine after administration of 80 ug/kg IV determined effects in the head height higher than 90%, 75% and 50% up to 2, 4 and 6 hours after administration. Meanwhile, the simulation of the effect of detomidine after the administration of 80 ug/kg IM determined effects in head height higher than 90%, 75% and 50% up to 3, 4 and 6 hours after administration. The present simulation showed that the effects of the position of the head after the administration of 80 ug/kg of detomidine via IV and IM in equines are superior and more prolonged when compared to the administration of 30 ug/kg. Therefore, in vivo studies should be performed in order to verify the adverse effects of these dosages in equines.
Keywords: Pharmacokinetic/pharmacodynamic modeling; alpha 2 agonists; clinical pharmacology